An effect of food additives on microbiome - V. Yu. Kornienko; M. Yu. Minaev (Теория и практика переработки мяса, 2021)
The paper presents a review of available data about an effect of food additives on the human microbiome and lists the main physiological functions of the gut microbiome. The process of the human microbiome evolution is examined. The relationship between the emergence of a disease and the microbiome composition, as well as the main factors influencing the gut microbiome composition are described. The main food additives used today are listed, their key features are discussed and their structural formulas are given. The information about their effect on the human body through an influence on the microbiome composition is presented. The data on an effect of polysorbate 80, carboxymethylcellulose, sodium sulfite, nisin, potassium sorbate, sodium benzoate, sodium nitrate, essential oils, titanium dioxide and different sweeteners on the microbiome are analyzed. It is explained what microbial communities are suppressed and what communities gain advantages in multiplication when consumers eat food with one or another food additive. The consequences of alterations in the microbiome for the consumer’s body are examined. Conclusions were made about the necessity of additional studies about an effect of food additives on the composition of the human microbiome.